Tyson : In and Out the Ring - Heller, Peter (London Pan Books, 1990)
The explosive no-holds-parred biography.
Include Appendices and Illustrations.
It is a biography of boxer Tyson.
Keywords: Tyson, Mike -- Boxing -- United States